The importance of human capital for the economic development of EU regions - Iwona Laskowska; Barbara Dańska-Borsiak (Comparative Economic Research. Central and Eastern Europe, 2016)
The EU designs its cohesion policy with the primary purpose of reducing disparities in regional development. The success of the policy is largely determined by the identification of factors that contribute to such disparities. One of the key determinants of economic success is human capital. This article examines the relationship between the quality of human capital and economic development of EU's regions. Using spatial analysis methods, the spatial dependencies between the growth of human capital and GDP per capita are investigated. According to the research results, the highest levels of human capital are typical of the most affluent regions in Western Europe, while its lowest levels are found in the poorest countries that became EU members only recently and in countries in southern Europe, including Greece. The spatial correlation measures confirm that spatial relationships have effect on the regional resources of human capital, showing that regions rich in human capital border on regions that are similar to them in that respect. The results of the spatial growth regression indicate that the amount of human capital in the region has a significant and positive effect on its GDP per capita.
Keywords: 330; European Union; regions; human capital; GDP per capita; Moran statistics; spatial regression; economic growth